Will Big Data Deliver its Promised Productivity Growth - Lionel Artige (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
There are high economic expectations concerning the emergence of Big Data: a promised golden age for both consumers and firms. Digital technology allows firms to provide digital services in exchange of personal data, from which they can finetune their supply to better match market demand. By extending Arrow (1962)'s analysis of the market for information to the phenomenon of Big Data, we propose a theoretical assessment of its potential effects on productivity growth. Our study highlights that Big Data modify the market for information by introducing new informational products which are not public goods. This characteristic is crucial as it implies that private production of personal-data based information can be profitable. This profitability gives digital firms the incentive to produce information likely to improve firm-level productivity and consumer welfare. Finally, we conclude that the productivity effect of Big Data at the macroeconomic level is conditional on both the production and diffusion of this personal-data based information.
Keywords: D8; L1; O4; 330; Big Data; competition; competition policy; economic growth; personal information; productivity